Carcinogenesis trajectories - Wang, Rui; Yan, Zhaopeng (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCancer origin patterns significantly influence cancer phenotypes and hallmark characteristics.MethodIn the present review, four distinct carcinogenesis trajectories that contribute to malignant transformation: mutator phenotype, chromosomal instability, dysmetabolism, and stemness, are explored.Results and DiscussionIn the mutator phenotype trajectory, deficiencies in DNA repair or synthesis systems lead to hypermutation and accumulation of oncogenic alterations. The chromosomal instability trajectory involves aneuploidy-induced copy number alterations in oncogenes and tumor suppressor genes. Dysmetabolic carcinogenesis is driven by the accumulation of oncometabolites due to alterations in metabolic genes. The stemness trajectory refers to the malignant transformation of cells possessing stem-like properties under oncogenic stimuli. Each trajectory independently promotes carcinogenesis and endows cancer cells with distinct characteristics. Notably, the primary oncogenic drivers in each trajectory can self-reinforce and form spontaneous-reinforcing loops that amplify oncogenic signals. Although crosstalk exists among trajectories, evidence suggests they are mutually exclusive during cancer origin. Therefore, targeting specific carcinogenesis trajectories and disrupting the self-reinforcing oncogenic loops may represent novel therapeutic strategies. Understanding carcinogenesis trajectories provides a framework for future cancer research and treatment approaches.